AN EXAMINATION OF THE 4C TEACHING METHOD IN ENHANCING 21ST-CENTURY SKILLS - Ilxomov Xojiakbar Iqboljon o’g’li (University Research Base, 2024)
This thesis explores the effectiveness and implications of the 4C teaching method in modern education. As the demands of the 21st century continue to evolve, the need for an educational approach that cultivates versatile skills beyond traditional knowledge becomes imperative. The four Cs competencies stimulate students' creativity as part of the application of creative competences based on some study findings. Implementing this particular method of teaching, however, still seems challenging due to some key issues and challenges. This thesis delves into the key issues and challenges of the 4C teaching strategy, investigates its practical implementation and efficiency in diverse educational settings.